Stability enhancement of organic photovoltaic devices utilizing partially reduced graphene oxide as the hole transport layer: nanoscale insight into structural/interfacial properties and aging effects. Issue 129 (16th December 2015) - Paci, B.; Kakavelakis, G.; Generosi, A.; Rossi Albertini, V.; Wright, J. P.; Ferrero, C.; Konios, D.; Stratakis, E.; Kymakis, E.
Abstract : A powerful insight into the structural and interfacial properties of post-fabricated bulk heterojunction (BHJ) organic photovoltaic (OPV) devices, utilizing partially reduced graphene oxide as the hole transport layer, is reported. Abstract : A powerful insight into the structural and interfacial properties of post-fabricated bulk heterojunction (BHJ) organic photovoltaic (OPV) devices is reported. The nanoscale local structure of integrated devices is revealed by combined X-ray diffraction (XRD) and fluorescence (XRF) investigations. A comparative study is performed on devices using graphene oxide (GO) as the hole transporting layer (HTL) and reference PEDOT:PSS (poly(3, 4 ethylenedioxythiophene):poly(styrenesulfonate)) devices. Spatially resolved simultaneous XRD/XRF measurements with nanometre resolution on pristine and aged states of the devices evidence the occurrence of morphological modifications in the poly(2, 7-carbazole) derivative (PCDTBT):fullerene derivative (PC71 BM) active layer, induced by thermal reduction and solar illumination. Additionally, the results indicate that OPV devices with partially reduced graphene oxide (pr-GO) used as the HTL, exhibit photovoltaic characteristics similar to the PEDOT:PSS based devices but with a significant durability enhancement. This is attributed to the protecting role of the pr-GO film against humidity and indium diffusion from the Indium Tin Oxide (ITO) anode into the photoactive layer. As a result, the devices fabricated with pr-GO-HTL retain approximately 65% of their initial power conversion efficiency over 20 hours, while the efficiency of the reference devices degrades to 45% of the initial value.